2009
DOI: 10.1111/j.1442-9993.2009.01987.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of species turnover in plant‐pollinator communities along a precipitation gradient in Patagonia (Argentina)

Abstract: Recent studies have assessed the influence of different types of gradients (e.g. altitudinal, latitudinal and temporal, among others) on the structure and function of community-level plant-pollinator webs. Although the importance of humidity as a major driver of species-richness gradients worldwide has been stressed by recent reviews, no studies have been specifically designed to address the influence of precipitation gradients on pollination webs. In the present paper we describe for the first time the turnov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 53 publications
3
17
0
Order By: Relevance
“…Linear relationship between Quaternary temperature-change velocity and nestedness in pollination networks on the mainland. Th is may result from either phenological shifts or range-size dynamics associated with climate-change between the LGM and the present (Price 2003, Memmott et al 2007, Ara ú jo et al 2008, Tylianakis et al 2008, Devoto et al 2009, Amano et al 2010, Nogu é s-Bravo et al 2010, Sandel et al 2011, possibly increasing the proportion of super-generalist ' network hub ' or ' connector ' species gluing the network together and blurring the borders between modules (Fig. To illustrate the global dataset, we also plotted island networks (n ϭ 31) as open symbols.…”
Section: Globalmentioning
confidence: 99%
See 3 more Smart Citations
“…Linear relationship between Quaternary temperature-change velocity and nestedness in pollination networks on the mainland. Th is may result from either phenological shifts or range-size dynamics associated with climate-change between the LGM and the present (Price 2003, Memmott et al 2007, Ara ú jo et al 2008, Tylianakis et al 2008, Devoto et al 2009, Amano et al 2010, Nogu é s-Bravo et al 2010, Sandel et al 2011, possibly increasing the proportion of super-generalist ' network hub ' or ' connector ' species gluing the network together and blurring the borders between modules (Fig. To illustrate the global dataset, we also plotted island networks (n ϭ 31) as open symbols.…”
Section: Globalmentioning
confidence: 99%
“…If indeed modularity decreases community persistence and nestedness increases resilience in pollination networks, the fi nding that pollination networks in climatically unstable North America and low-laying part of northern Europe have a low level of modularity and often relatively high level of nestedness (Fig. In light of the current anthropogenic climate-change and the global decline of pollinators and possible interlinked plant declines (Biesmeijer et al 2006, Devoto et al 2009), more research is clearly needed to address in detail the processes beneath the relationship between historical climate-change, modularity, nestedness and stability of pollination networks. In light of the current anthropogenic climate-change and the global decline of pollinators and possible interlinked plant declines (Biesmeijer et al 2006, Devoto et al 2009), more research is clearly needed to address in detail the processes beneath the relationship between historical climate-change, modularity, nestedness and stability of pollination networks.…”
Section: Globalmentioning
confidence: 99%
See 2 more Smart Citations
“…Traditional investigations of plant communities have shown that plant species typically have nonrandom distributions through space at the spatial scale at which plant-pollinator networks are often quantified (,10 6 m 2 ; Kissling et al 2012) and are structured largely by microhabitat gradients, temperature, and precipitation (Kikvidze et al 2005). Likewise, pollinator species have a high degree of spatial, temporal, and environmental turnover (Minckley et al 1999, Devoto et al 2009). The interaction network approach to studying plant-pollinator communities has provided evidence of extremely high variability in plant-pollinator interactions between years (Petanidou et al 2008, Olesen et al 2011, with interannual interaction persistence ranging from 1.4-22% (Dupont et al 2009, Fang andHuang 2012).…”
Section: Introductionmentioning
confidence: 99%